Genome Sequencing and Assembly Strategies and a Comparative Analysis of the Genomic Characteristics in Penaeid Shrimp Species - Yuan, Jianbo; Zhang, Xiaojun; Li, Fuhua; Xiang, Jianhai (Frontiers in Genetics, 2021)
Penaeid shrimp (family Penaeidae) represents one of the most economically and ecologically important groups of crustaceans. However, their genome sequencing and assembly have encountered extreme difficulties during the last twenty years. In this study, based on our previous genomic data, we investigated the genomic characteristics of four penaeid shrimp species, and identified potential factors resulting for the poor genome assembly of them, including heterozygosity, polyploidization and repeats. Genome sequencing and comparison of somatic cells (diploid) and single sperm cells (haploid) identified a common bimodal distribution of K-mer depths in the four shrimp species, suggesting either high heterozygosity or abundant homo-duplicated sequences present in their genomes. However, penaeids have not undergone whole genome duplication as indicated by a series of approaches. Besides, the remarkable expansion of simple sequence repeats was another outstanding character of penaeid genomes, which also made the genome assembly highly fragmented. Due to this situation, various genome sequencing and assembly strategies were conducted and compared to find a better way to obtain high-quality genome of penaeid shrimp. Therefore, this study provides some clues for understanding genomic characteristics of penaied shrimp better, and also upgrading genome assembly of them.